2018
DOI: 10.1002/btm2.10113
|View full text |Cite
|
Sign up to set email alerts
|

A platform of genetically engineered bacteria as vehicles for localized delivery of therapeutics: Toward applications for Crohn's disease

Abstract: For therapies targeting diseases of the gastrointestinal tract, we and others envision probiotic bacteria that synthesize and excrete biotherapeutics at disease sites. Toward this goal, we have engineered commensal E. coli that selectively synthesize and secrete a model biotherapeutic in the presence of nitric oxide (NO), an intestinal biomarker for Crohn's disease (CD). This is accomplished by co‐expressing the pore forming protein TolAIII with the biologic, granulocyte macrophage‐colony stimulating factor (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 101 publications
(229 reference statements)
0
34
0
Order By: Relevance
“…In particular, it is shown that short hairpin RNA (shRNA) expressing bacteria elicit RNAi in mammals [87], rendering bacteria-mediated RNAi-based diagnosis and therapeutics a promising prospect [88]. In this respect, recently, McKay et al [89] proposed a platform of genetically engineered bacteria as vehicles for localized delivery of therapeutics toward applications for Crohn's disease. From MC perspective, genetically engineered bacteria have been envisioned to be utilized in various ways with different transmitter architectures.…”
Section: ) Information-carrying Moleculesmentioning
confidence: 99%
“…In particular, it is shown that short hairpin RNA (shRNA) expressing bacteria elicit RNAi in mammals [87], rendering bacteria-mediated RNAi-based diagnosis and therapeutics a promising prospect [88]. In this respect, recently, McKay et al [89] proposed a platform of genetically engineered bacteria as vehicles for localized delivery of therapeutics toward applications for Crohn's disease. From MC perspective, genetically engineered bacteria have been envisioned to be utilized in various ways with different transmitter architectures.…”
Section: ) Information-carrying Moleculesmentioning
confidence: 99%
“…Recently, a genetic circuit based on NO detection, pseudotaxis and secretion was created in E. coli to produce and export granulocyte macrophage-colony stimulating factor (GM-CSF) in situ (McKay et al, 2018). NO activated the expression of CheZ, a motility regulator protein in an E. coli strain otherwise lacking this gene.…”
Section: Sense and Respond Systemsmentioning
confidence: 99%
“…Unfortunately, environmental complexity and a continuous flow within the GI tract render low oral bioavailability and limited intestinal colonization. Previously, bacteria with increased resistance have been engineered to improve stomach survival (13). Instead of focusing on genetic engineering, surface modification endows an effective approach to decorate bacteria with functional motifs (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%